Additive Manufacturing on the Façade: Functional use of Direct Metal Laser Sintering Hatch Distance Process Parameters in Building Envelope - Çalışkan, Cemal İrfan; Arpacıoğlu, Ümit (Emerald Group Publishing Ltd, 2022)
Purpose – The purpose of this article is on the functional usability of metal additive manufacturing (AM) direct metal laser sintering (DMLS) production technology process parameters in the construction industry. In the study, the advantages of thermal optimization and weight reduction in the case of the use of foam metals obtained by changing the hatch distance the production process parameter, in the production of facade panels in the architectural field are revealed. Design/methodology/approach – The methods in the study; production of the small scaled facade panels with nine different hatch distance parameters, determination of the thermal change with the infrared thermography method, microstructure examination, weight measurement. Findings – The paper lays the groundwork for the manufacturability of lighter and lower thermal conductivity facade panels by changing the hatch distance parameters. Within the scope of the study, the definition of semi-open-cell foam aluminum and the product screening strategy offers innovation. Within the scope of the study, this scope is shared as an algorithmic summary. In addition, the study offers a new perspective within the scope of multiple optimizable panel production in facade panels with AM technology. Originality/value – Hatch distance parameter change was first discussed in this study in the architectural field, and a semi-open cell foam aluminum panel was obtained with the scanning strategy determined within the scope of the study. This panel geometry, which is defined as semiopen cell foam aluminum, can be used as a design element by painting or coating the outer surface, it can be stated that it will also provide thermal and weight optimization.
Keywords: Additive Manufacturing (AM); Direct Metal Laser Sintering (DMLS); Process Parameters; Architecture; Façade